An algorithmic of analog-to-digital converter using current-mode and digital CMOS process - Oki, N. (IEEE Computer Soc, 1999)
In this paper a new algorithmic of Analog-to-Digital Converter is presented. This new topology use the current-mode technique that allows a large dynamic range and can be implemented in digital CMOS process. The ADC proposed is very small and can handle high sampling rates. Simulation results using a 1.2um CMOS process show that an 8-b ADC can support a sampling rate of 50MHz.